General defense system in the plant kingdom - Szarka, J.; Csilléry, G. (International Journal of Horticultural Science, 2001)
The goal of plant breeders is to improve the resistance of crops against virus, bacterium and fungus pathogens was easiest to achieve by selection for phenotypes displaying the hypersensitive reaction. The resistant plant of that type keeps its health by preventing or delaying the systemization of the pathogen by destruction of cells and tissues of variable size or amputation of the contaminated organs. The faster the reaction of the host plant is the more efficient and economical is the defense, since the extent of tissue destruction decreases proportionally with the speed of reaction.During a breeding program for resistance carried out on several plant species, mainly vegetables over thirty years, also an alternative defense reaction has been experienced, which fundamentally differs from the hypersensitive reaction. In that reaction the cells and tissues of the host plant being exposed to the pathogen do not die, on the contrary they hinder systemization of the pathogen by tissue thickening. An additional significant difference is that on the contrary to hypersensitive reaction this reaction is less host- or pathogen-specific and works excellently even at high temperature (over 40 °C).